Outcomes in Delayed Drainage of Hemothorax. Issue 7 (July 2021) - Weaver, Jessica L.; Kaufman, Elinore J.; Young, Andrew J.; Keating, Jane J.; Subramanian, Madhu; Cannon, Jeremy W.; Shiroff, Adam; Seamon, Mark J.
Background: Prompt drainage of traumatic hemothorax is recommended to prevent empyema and trapped lung. Some patients do not present the day of their trauma, leading to their delayed treatment. Delayed drainage could be challenging as clotted blood may not evacuate through a standard chest tube. We hypothesized that such delays would increase the need for surgery or secondary interventions. Methods: Our trauma registry was reviewed for patients with a hemothorax admitted to our level 1 trauma center from 1/1/00 to 4/30/19. Patients were included in the delayed group if they received a drainage procedure >24 hours after injury. These patients were matched 1:1 by chest abbreviated injury score to patients who received drainage <24 hours from injury. Results: A total of 19 patients with 22 hemothoraces received delayed drainage. All but 3 patients had a chest tube placed as initial treatment. Four patients received surgery, including 3 who initially had chest tubes placed. Longer time to drainage increased the odds of requiring intrathoracic thrombolytics or surgery. In comparison, 2 patients who received prompt drainage received thrombolytics ( P = .11) and none required surgery ( P = .02). Patients needed surgery when initial drainage was on or after post-injury day 5, but pigtail catheter drainage was effective 26 days after injury. Discussion: Longer times from injury to intervention are associated with increased likelihood of needing surgery for hemothorax evacuation, but outcomes were not uniform. A larger, multicenter study will be necessary to provide better characterization of treatment outcomes for these patients.